CONCEPTS OF THE TEACHING OF LANGUAGE STRUCTURES AND LIMITED CONVERSATION - Xаlikоvа, Latofat (Журнал иностранных языков и лингвистики, 2023)
This thesis deals with linguistic structures and limited conversation in practice. Our conversation is about different types of design. This work opens up the answer design, the network remains hidden and the student is challenged to generate the appropriate answer without any cues from the system.